Prohibition and Sanctions for Beggars: A Juridical Review - Hau, Lucia de Canossa Silva; Wirawan, Ketut Adi (Verdict: Journal of Law Science, 2025)
The phenomenon of beggars in public spaces has become a social and legal issue that continues to evolve in Indonesia. On one hand, begging is viewed as an expression of economic necessity among marginalized communities; on the other hand, its presence is often considered to create social problems that require legal intervention. This study aims to address two main research questions: (1) how sanctions for beggars are regulated in Indonesia; and (2) what legal consequences arise when someone gives money to beggars. This research employs a normative juridical method with statutory and conceptual approaches to examine relevant legal provisions in the Indonesian Criminal Code (KUHP), Regional Regulations (Peraturan Daerah), and scholarly literature. The findings indicate that regulations concerning beggars are not specifically stipulated in the KUHP, but many regions have established provisions within Regional Regulations on public order. Sanctions for beggars may include imprisonment, administrative fines, and social rehabilitation. Meanwhile, individuals who give money to beggars are generally not subject to direct criminal penalties, although some Regional Regulations extend the prohibition by imposing sanctions on givers as well. This study concludes that regulations concerning beggars largely depend on regional authority and are administrative in nature, thereby highlighting the need for policy harmonization to ensure a more effective approach in addressing the issue of begging.